1881-82 Va. Acts 233, ch. 219, § 1 - (:unkn) unknown (My University, 1881)
Prohibited the conceal carry of any pistol, dirk, Bowie-knife, or any weapon of the like kind. Violators fined not more than fifty dollars, nor less than fifteen dollars.
Keywords: CARRY - CONCEALED